The Burden of proof : the Vargas-Laurel collaboration case - Agoncillo, Teodoro A.; Vargas, Jorge B. (Mandaluyong City, Philippines : University of the Philippines Press for the U.P.-Jorge B. Vargas Filipiniana Research Center, 1984)
WHEN I WAS preparing my The Fateful Years: Japan's Adventure in the Philippines, 1941-1945 (Quezon City, 1965, 2 volumes) in the early 1960s, I thought of including a chapter on the question of collaboration with emphasis on the roles played by Jorge B. Vargas and José P. Laurel. But Mr. Vargas' reluctance coupled with the death of Laurel and Recto earlier, made me change my mind. The rest of those involved in the question, although they played but minor roles, were either too busy with political and not-so-political activities or were too preoccupied with the problems of dealing with the difficult and exasperating aspects of life to pay any serious attention to scholarly pursuits. In the meantime, I continued collecting materials on the subject and filed them away as part of the archival materials I had accumulated over the years. When, in early 1979, Mr. Vargas, now advanced in age, expressed his willingness to make a clean breast of the whole business of collaboration with the Japanese military during the war years, I thought of resuscitating my plan to write on the subject but on a wider scale. Someone reminded me that an American historian had already written a doctoral dissertation on the subject.
1. THE LAST INSTRUCTIONS --2. TRANSITION: THE VARGAS PREDICAMENT --3. INDEPENDENCE: THE LAUREL CALVARY --4. THE FLIGHT TO TOKYO --5. INSIDE SUGAMO --6. THE NATIVES RETURN --7. THE STORM OVER COLLABORATION --8. THE ENCOUNTER --9. AMNESTY --10. IN RETROSPECT.
Includes bibliographical references and index.
Keywords: COLLABORATION CASE